QUALITY ISLAMIC EDUCATION IN A MULTICULTURAL SOCIETY: A BIBLIOMETRIC STUDY AND LITERATURE REVIEW - Elihami Elihami (International Conference on Social and Islamic Studies, 2021)
This research aims to look at the quality of Islamic education in a multicultural society in terms of learning outcomes. The descriptive approach of "bibliometric analysis" was utilized to accomplish this. It examined (233) scientific studies over ten years (2010-2021) and critically evaluated them in light of the study questions in order to identify the variables that these studies sought to investigate on the strategy, their impact on those variables, and the justification for the strategy's positive impact. According to the findings, the flipped classroom may give students a more dynamic learning environment, resulting in increased learning accomplishment and better preparedness for 21st-century learning and job situations. Much of the research examined the benefits and advantages of this method and the relevance of implementing it at various levels of education due to its demonstrable results in increasing a variety of learning outcomes. The research advised that instructors adopt the flipped classroom technique more often because of its favourable influence on learning outcomes. It also recommended pursuing research into the causes for the strategy's lack of evident beneficial effect in other trials.